Description of Adjustment in Mothers Who Experience Empty Nest Syndrome - Putri, Hasri Apriliany; Siswanti, Dian Novita; Jafar, Eka Sufartianinsih (Polteknik Ilmu Pemasyarakatan, 2023)
Middle adulthood will experience a phase when children have entered the adult age stage and leave home to get married, work, or continue their education. This phase makes parents, especially mothers, sad and feel lonely because they have not been able to accept the departure of their children, so they experience empty nest syndrome. This study aims to determine the description of adjustment in housewives who experience empty nest syndrome. The method in this research uses qualitative research methods with a case study approach. The subjects of this research were three middle adults who played the role of housewives with an age range of 50-58 years. Data collection was carried out through a process of interviews, observation and documentation. The results of the research showed that the three subjects experienced the characteristics of empty nest syndrome and a picture of adjustment according to the conditions that affected each subject. The three subjects carried out household activities as usual and added new hobbies as a way to control themselves with the empty nest situation they faced. All three subjects had people closest to them who provided support so that they were able to adjust to the departure of their children from home. The conclusion from the research results is that there were 3 research subjects, namely Mrs. S, Mrs. R and Mrs. N who experienced the characteristics of empty nest syndrome and a description of their adjustment according to the conditions that affected each subject. The three subjects carried out household activities as usual and added new hobbies as a way to control themselves with the empty nest situation they faced. All three subjects had people closest to them who provided support so that they were able to adjust to the departure of their children from home.